The 2017 Reversal of the Beaufort Gyre: Can Dynamic Thickening of a Seasonal Ice Cover During a Reversal Limit Summer Ice Melt in the Beaufort Sea?. Issue 12 (8th December 2020) - Babb, D. G.; Landy, J. C.; Lukovich, J. V.; Haas, C.; Hendricks, S.; Barber, D. G.; Galley, R. J.
Abstract: During winter 2017, the semipermanent Beaufort High collapsed and the anticyclonic Beaufort Gyre reversed. The reversal drove eastward ice motion through the Western Arctic, causing sea ice to converge against Banks Island, and halted the circulation of multiyear sea ice via the gyre, preventing its replenishment in the Beaufort Sea. Prior to the reversal, an anomalously thin seasonal ice cover had formed in the Beaufort following ice‐free conditions during September 2016. With the onset of the reversal in January 2017, convergence drove uncharacteristic dynamic thickening during winter. By the end of March, despite seasonal ice comprising 97% of the ice cover, the reversal created the thickest, roughest, and most voluminous regional ice cover of the CryoSat‐2 record. Within the Beaufort Sea, previous work has shown that winter ice export can precondition the region for increased summer ice melt, but that a short reversal during April 2013 contributed to a reduction in summer ice loss. Hence, the deformed ice cover at the end of winter 2017 could be expected to limit summer melt. In spite of this, the Beaufort ice cover fell to its fourth lowest September area as the gyre re‐established during April and divergent ice drift broke up the pack, negating the reversal's earlier preconditioning. Our work highlights that dynamic winter thickening of a regional sea ice cover, for instance during a gyre reversal, offers the potential to limit summer ice loss, but that dynamic forcing during spring dictates whether this conditioning carries through to the melt season. Plain Language Summary: The Beaufort Gyre is a semipermanent feature that transports sea ice clockwise from the High Arctic through the Beaufort and Chukchi Seas. Occasionally the Gyre reverses, transporting sea ice counterclockwise. Historically these reversals only occurred during summer, but as the arctic changes reversals have become more frequent and more pronounced, and during winter 2017, the gyre underwent a prolonged reversal. Using a mix of satellite‐based and in situ observations, we examine how this reversal affected the ice cover of the Western Arctic. By altering the patterns of sea ice motion and forcing sea ice in the Beaufort Sea to converge against the coast, the reversal transformed the ice cover from an anomalously thin seasonal ice cover in fall to an anomalously thick and rough ice cover by the end of winter. Theoretically this conditioned the ice cover for limited summer ice loss. However, this was not the case as the ice cover broke up prematurely during spring, allowing the sun to warm surface waters and melt the ice through the ice‐albedo feedback. By September, the ice cover fell to its fourth lowest regional minimum as the Beaufort ice cover continues to decline. Key Points: The Beaufort Gyre reversal during winter 2017 drove anomalous sea ice convergence against the Canadian Arctic in the Beaufort Sea Deformation transformed an anomalously thin seasonal ice cover into the roughest and thickest end of winter ice pack in the CryoSat‐2 record Despite being conditioned to limit summer melt, spring dynamics broke up the ice pack and led to another low ice year in the Beaufort Sea